Chronic pulmonary aspergillosis in tea population of Assam. - Aishwarya Selvasekhar; Reema Nath; Gourangie Gogoi; Pronami Borah (PLoS Neglected Tropical Diseases)
Background Chronic pulmonary aspergillosis (CPA) is a disease commonly caused by Aspergillus fumigatus and other Aspergillus species characterized by cavitary lung lesions. Tea garden population is an agrarian population of Assam, mostly associated with tea plantations. Assam is a major tea-producing state with 803 tea gardens producing approximately 50% of the total tea in India, of which 177 are present in the Dibrugarh district alone. Tuberculosis is common in tea garden workers. This community-based cross-sectional study in the tea garden community of Dibrugarh was done to find the prevalence of Aspergillus IgG antibodies and CPA cases in individuals with chronic respiratory symptoms. Methodology and principal findings Patients visiting 3 tea garden hospitals and 2 referral hospitals with chronic cough and/or haemoptysis, weight loss/fatigue, and other respiratory symptoms for a duration of 3 months or more were included in this one-year study. Serum samples were tested by Immunocap Phadia 200 for Aspergillus fumigatus-specific IgG antibodies. CPA cases were diagnosed based on clinical, radiological, and serological criteria. Out of 128 samples, seropositivity was seen in 41 (32.0%) patients (cutoff value: 27 mgA/l). Male preponderance (1.6:1) with a mean age of 41.9 (±15.69) was observed. Haemoptysis and fatigue were significant symptoms seen (p-values: 0.0086 and 0.0098, respectively). Aspergillus fumigatus-specific IgG antibody was found to be significantly high in 29 out of 76 patients (38.1%) with a history of tuberculosis. Amongst them, seropositivity with active TB was 5 out of 27 patients (18.5%), and seropositivity with post-TB was 24 out of 49 patients (48.9%). Chronic cavitary pulmonary aspergillosis was the predominant type (38.1%). Proven CPA (clinically, radiologically, and serologically positive) were 22 (17.1%, 95% CI 10.7%-26.0%), and possible CPA (clinically and serologically positive but without radiological data) were 19 (14.8%, 95% CI 8.9%-23.1%). Conclusion A high prevalence of CPA (60 per 100 000) was detected. High Aspergillus seropositivity of 48.9% was seen in the post-TB population. Aspergillus-specific IgG antibody testing is the only confirmatory method for diagnosing CPA, which is available in limited centres in India. Aspergillus seropositivity should be detected in post-TB patients presenting with chronic respiratory symptoms.